When Angels Dance for Kings: The beginning of Scandinavian music theatre - Rygg, Kristin (Danish Yearbook of Musicology, 2012)
The first music theatre performance in Scandinavia, the so called ballet given at the royal wedding in Copenhagen in 1634, is explored in this article. The first main question is what the royal family and the various artists working for them wanted to achieve by staging this ballet. The second main question is how this onset of Scandinavian music theatre was related to leading traditions of courtly music theatre in other North European courts, primarily those in England and France. In this connection Mara Wade’s interpretations of the Copenhagen ballet in her study Triumphus nuptialis are discussed. The article shows that as far as form is concerned, the Copenhagen performance is clearly structured like a French ballet de cour. However, the actual contents demonstrates that the potentiality of the performance as political propaganda is hardly exploited, whereas signs linked to occult trends like alchemy and Rosicrucianism are manifold, indicating that these trends were essential to at least parts of the royal family itself. In this respect the first music theatre performance in Scandinavia also shows surprising influence from the English court masque.